2015
DOI: 10.1002/hec.3159
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Near‐Universal Insurance Coverage on Breast and Cervical Cancer Screening: Evidence from Massachusetts

Abstract: This paper investigates the effect of expansion to near-universal health insurance coverage in Massachusetts on breast and cervical cancer screening. We use data from 2002 to 2010 to compare changes in receipt of mammograms and Pap tests in Massachusetts relative to other New England states. We also consider the effect specifically among low-income women. We find positive effects of Massachusetts health reform on cancer screening, suggesting a 4 to 5% increase in mammograms and 6 to 7% increase in Pap tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…While some studies found that access to insurance increased cancer screening, others found that the impact of insurance on cancer screening and detection varied by tumor site or the length of follow-up after a policy change (Han, Zang Xiong, Kramer, & Jemal, 2016;Kolstad & Kowalski, 2012;Robbins et al, 2015;Sabik & Bradley, 2016;Soni, Simon, Cawley, & Sabik, 2017). The Oregon Health Insurance Experiment, a randomized expansion of Medicaid insurance, found that insurance increased cancer screening, but cancer detection and outcomes were not assessed (Baicker et al, 2013;Conlin, Allen, Tsui, Carlson, & Li, 2016).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…While some studies found that access to insurance increased cancer screening, others found that the impact of insurance on cancer screening and detection varied by tumor site or the length of follow-up after a policy change (Han, Zang Xiong, Kramer, & Jemal, 2016;Kolstad & Kowalski, 2012;Robbins et al, 2015;Sabik & Bradley, 2016;Soni, Simon, Cawley, & Sabik, 2017). The Oregon Health Insurance Experiment, a randomized expansion of Medicaid insurance, found that insurance increased cancer screening, but cancer detection and outcomes were not assessed (Baicker et al, 2013;Conlin, Allen, Tsui, Carlson, & Li, 2016).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…As in previous studies on mammography use (Bitler & Carpenter, 2016a, 2016bCarrieri & Wuebker, 2016;Pletscher, 2017;Sabik & Bradley, 2016) our dependent variables are based on self-reports. In the first two waves, the ESPS asks women whether they ever had a mammogram.…”
Section: Data: the Enquête Santé Et Protection Socialementioning
confidence: 99%
“…Busch and Duchovny (2005) and Finkelstein et al (2012) find a positive effect of Medicaid. Several recent studies examine the effect of Massachusetts's 2006 health reform on mammography use and obtain mixed results(Keating et al, 2013;Kolstad & Kowalski, 2012;Sabik & Bradley, 2016).3 In addition to France, the Netherlands extends the target age range to 74. In Ireland and Estonia, the upper age limit is 64 and 65, respectively.…”
mentioning
confidence: 99%
“…There is limited evidence regarding the effects of public insurance coverage expansions to the nonelderly on cervical cancer screening. Evidence from insurance expansions under Massachusetts health reform shows significant increases in Pap tests, particularly among low‐income women (Sabik and Bradley ). Two studies that consider the effects of Medicaid expansions specifically also find significant positive effects.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributable to the program's limited budget and uninsured women's lack of awareness of program benefits. In contrast, evidence from coverage expansions under Massachusetts health reform suggests that near‐universal coverage increases cancer screening, indicating an impact of comprehensive coverage beyond that of safety net programs in existence prior to expansion (Sabik and Bradley ). We hypothesize that full Medicaid coverage that may promote engagement with the health care and link women to primary care will increase use of preventive services such as cervical cancer screening, despite the presence of the family planning and NBCCEDP programs.…”
mentioning
confidence: 99%